Al-MCM-41: An Efficient and Recyclable Heterogeneous Catalyst for the Synthesis of β-Hydroxy Thiocyanates in Water. (16th October 2012) - Sayyahi, Soheil; Menati, Saied; Karamipour, Mehri
Abstract : An efficient and green procedure has been developed for the synthesis of β -hydroxy thiocyanate by the regioselective ring opening of epoxides with NH4 SCN. The reaction was carried out in water without any organic solvent at 40 ° C, using Al-MCM-41 (a mesoporous aluminosilicate) as catalyst. In this method, several types of epoxides carrying electron-donating or withdrawing groups were rapidly converted to the corresponding β -hydroxy thiocyanates in good from excellent yields. Various advantages associated with this protocol include simple workup procedure, short reaction times, high product yields, greater regioselectivity, and easy recovery and reusability of the catalyst.